Evaluation of shear bond strength of three different types of artificial teeth to heat cure denture base resin: An in vitro study - B Chittaranjan; M Taruna; N Sudheer; Nagesh S Patil (Wolters Kluwer Medknow Publications, 2013)
Context: Bonding of artificial teeth and denture base material remained a significant problem for successful prosthetic treatment. Aim: The purpose of this in vitro study was to evaluate shear bond strength of three different artificial teeth with heat cure denture base material after various surface conditioning methods and thermocycling. Materials and Methods: Ninety mandibular first molar denture teeth were selected. They were divided into three groups, Group I: Nanocomposite resin (Veracia), Group II: Composite teeth (Endura), and Group III: Cross-linked acrylic denture teeth (Acry rock). All groups were further subdivided into subgroups based on surface conditioning methods. Subgroup A: No surface conditioning (control group), Subgroup B: Surface conditioning with methyl methacrylate-based bonding agent (Vitacoll), and Subgroup C: Air abrasion with 50 μm aluminum oxide powder particles plus silane-coupling agent (Monobond-S) and Vitacoll bonding agent. Evaluation of shear bond strength of all the specimens was done using universal testing machine. Results: Mean shear bond strength of Group I, Subgroup B (6.87 ± 0.934) showed higher value when compared with Group II, Subgroup B (6.76 ± 1.84) and Group III, Subgroup B (5.66 ± 2.18). The control group (untreated surface) of all three types of artificial teeth used in this study showed significantly lower shear bond strength values than experimental groups (surface conditioning methods; P < 0.05). Conclusion: The results of this study suggest that there were significant differences in shear bond strength among control group and surface treatment groups of denture teeth bonded to heat cure denture base resin.